2006
DOI: 10.1299/jbse.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production and Smooth Muscle Cell Phenotype of Endothelial Cell-Smooth Muscle Cell Cocultured Model

Abstract: This study investigated nitric oxide (NO) production and phenotype changes of smooth muscle cells (SMC) in a cocultured model (CM) exposed to fluid shear stress. The CM was composed of human umbilical endothelial cells (EC) and SMC, a collagen layer, and a porous membrane. After exposing the CM to shear stress of 1.5 Pa for 24 hours, α-smooth muscle actin (α-SMA) expression of SMC and NO production in culture media were examined. Under static conditions, α-SMA expression in the CM was significantly lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
4
7
1
Order By: Relevance
“…3). This phenotypic change of SMCs was the same as that observed in previous studies [8,9]. The maximum expression of α-SMA and calponin in SMCs occurred on QM6, as shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…3). This phenotypic change of SMCs was the same as that observed in previous studies [8,9]. The maximum expression of α-SMA and calponin in SMCs occurred on QM6, as shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The maximum expression of α-SMA and calponin in SMCs occurred on QM6, as shown in Fig. 2, which is the same result as that obtained with two-dimensionally-cultured SMCs [9]. In this study, the expression of another contractile protein, MHC, was also examined, and the results showed that the maximum expression of MHC in SMCs occurred on QM12, which was later than that of α-SMA and calponin (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations